Kinetics and mechanism of the hydrolysis of 1-(1-N-Methyliminoethyl)-2-naphthol - Ee, Gwendoline Cheng Lian; Main, Lyndsa Y. (1982)
Kinetic studies have not previously been made of the hydrolysis of imines derived from 2'-hydroxy ace tonaphthones. We report here on the methyl imine l-(l-Nmethyliminoethyl)- 2-naphthol derived from 2' -hydroxyl'- acetonaphthone and account for its pH rate profile, which is quite different from that previously reported' for the ethyl imine o-(1-N-ethyliminoethyl)phenol derived from 2' -hydroxyacetophenone.